ZOUK, LAMBADA, LAMBAZOUK, BRAZILIAN ZOUK - MYTHS, TRUTHS AND EVOLUTION - Barbosa Ramos, Nairo (Revista Gênero e Interdisciplinaridade, 2024)
This article investigates the differences between zouk, lambada and lambazouk, analyzing their origins, evolutions and myths. It is argued that zouk is a musical style originating from the French West Indies and that lambazouk is a version of lambada with new movements influenced by other styles and dances, danced to the sound of zouk music and other musical genres. The analysis is based on scientific and empirical evidence, highlighting that lambada adapts to different musical genres, but maintains its essential characteristics. Lambada is highlighted as a genuinely Brazilian dance and a cultural heritage of Porto Seguro.